Regulations To Be Made In Urban Areas In Order To Improve Accessibility Of The “Visually-Impaired - Pelin Gökgür (Konya Technical University Faculty of Architecture and Design, 2014)
In our country, disabled people encounter many problems in integrating with the city and city life. The most important one is the "accessibility" in the physical space. Providing accessibility require disabled to move without being in need of any help, without any prevention and to participate in the life activities. It is seen in our country that the obstacle-free walkways for the disabled do not exist in the cities including the pedestrian areas, the legal arrangements with respect thereto are not yet able to achieve the required conditions in the physical environment, and the required sanctions and controls are not sufficient. Moreover, inability to present accurately the difference in the needs as based on the disability type is exposed in the problems that occur in the arrangements realized. The basic needs of "visually-impaired" people in the urban space, which constitutes the subject matter of the study can be listed as; safety, to understand where s/he is going, to know where s/he is and to obtain information about the surrounding. For the visually-impaired people to obtain such needs depends on their ability to move alone in the urban space. One of the most important issues in achieving this is "orientation". "Orientation" involves the process of determination of the person's own position and relation with the important objects around. It is known that the "accessibility" of a visually-impaired person is based on orientation and the arrangements in the physical environment in achieving this are very important. In this study, the purpose is to present the significance of "orientation" directed to increase the accessibility of the "visually-impaired" people in the urban space and as based on this, to discuss "the arrangements required to be realized in the physical environment”.